2011
DOI: 10.1097/tp.0b013e31823817d5
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent and Decision-Making About Adult-to-Adult Living Donor Liver Transplantation: A Systematic Review of Empirical Research

Abstract: Adult-to-adult living donor liver transplantation (LDLT) is a complex procedure that poses serious health risks to and provides no direct health benefit for the donor. Because of this uneven risk-benefit ratio, ensuring donor autonomy through informed consent is critical. To assess the current knowledge pertaining to informed consent for LDLT, we conducted a systematic review of the empirical literature on donors' decision-making process, comprehension about risks and outcomes, and information needs for LDLT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…However, Valapour and colleagues found considerably higher rates (40%) of LKDs reporting some pressure to donate, and that significantly greater pressure was felt among those donating to related than to unrelated recipients (52). In a systematic review of LLDs, rates of undue pressure were found to vary internationally, with lowest rates in the US (<4%), moderate rates in Europe (<14%), and highest rates in Asian countries (5-20%) (23).…”
Section: Voluntarinessmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Valapour and colleagues found considerably higher rates (40%) of LKDs reporting some pressure to donate, and that significantly greater pressure was felt among those donating to related than to unrelated recipients (52). In a systematic review of LLDs, rates of undue pressure were found to vary internationally, with lowest rates in the US (<4%), moderate rates in Europe (<14%), and highest rates in Asian countries (5-20%) (23).…”
Section: Voluntarinessmentioning
confidence: 99%
“…Paradoxically, while LKDs generally highly understand the short-term medical risks of donation, they tend to poorly understand the psychosocial, medical, long-term and financial risks of donation (52). Similarly, a recent systematic review of informed consent for LLDs found that most LDs reported high levels of comprehension (up to 94% of donors) of information disclosed about the donation process and risks (23). However, studies also found LLDs' gaps in knowledge and perceptions of the magnitude of risks involved in hepatectomy (53)(54)(55)(56)(57)(58)(59).…”
Section: Comprehension and Information Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, systematic reviews indicate that prospective living liver donors are not sufficiently informed and do not adequately comprehend the information that they receive about donation procedures and associated risks. 3,4 Thus, there is a great need to provide standardized information to prospective living liver donors to supplement the current informed consent process. Currently, there is no standardized approach to information disclosure for informed consent in this population.…”
mentioning
confidence: 99%